PROSES PEMBEBANAN HAK TANGGUNGAN PADA SERTIFIKAT HAK MILIK DALAM PERIKATAN JAMINAN KREDIT - Rina Laksmita Putri, Luh Putu; Novy Purwanto, I Wayan (Kertha Semaya : Journal Ilmu Hukum, 2014)
Writing is the process of loading encumbrance on the land title loanguarantee commitment. In this paper aims to understand and know about theprocess of loading encumbrance on the property certificate credit commitmentand the legal guarantees of security rights. This research uses a method ofnormative reference to the applicable law. This paper can produce a conclusionthat the loading process is basically the right to be preceded by a subsequentagreement registered in National Land Agency through the land registry for theissuance of certificates could Mortgage by National Land Agency. MortgageCertificate binding legal effect (executorial) same position with the court ruling.
Keywords: Guarantee Credit, Mortgage Imposition